2013
DOI: 10.1080/ac.68.2.2967274
|View full text |Cite
|
Sign up to set email alerts
|

Detection of myocardial injury due to defi brillation threshold checking after insertion of implantable cardioverter/defi brillators

Abstract: Elevation of cTNT and CK-MB after the ICD implantation was significantly higher than that after the PPM implantation and may be attributed to the DFT testing shock and resulting myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Although cTnI increased in both DFT+ and DFT− groups in our study, DFT+ patients had higher levels of cTnI release compared to the DFT− group, likely associated with the defibrillation shock. Our results, similar to other studies, 13,15,16 contrast with those of Furniss et al 14 who used a control group with DFT only (at time of ICD generator change) and found no troponin elevation associated with defibrillation. This discrepancy may be related to the lower number of patients included in their study, as well as the lower energy delivered with a single shock.…”
Section: Troponin Increasesupporting
confidence: 90%
“…Although cTnI increased in both DFT+ and DFT− groups in our study, DFT+ patients had higher levels of cTnI release compared to the DFT− group, likely associated with the defibrillation shock. Our results, similar to other studies, 13,15,16 contrast with those of Furniss et al 14 who used a control group with DFT only (at time of ICD generator change) and found no troponin elevation associated with defibrillation. This discrepancy may be related to the lower number of patients included in their study, as well as the lower energy delivered with a single shock.…”
Section: Troponin Increasesupporting
confidence: 90%
“…11 Davoodi et al found that DFT test shock might result in myocardial injury. 12 In the Sham'a et al study, troponin elevation occurred in most of patients after inappropriate ICD shock because of lead fracture. 13 Therefore, it was proven that ICD shock causes myocardial damage, and the severity of the myocardial damage is related to the defibrillation energy.…”
Section: Discussionmentioning
confidence: 98%
“…"Catecholamine overload" (ref. [27][28][29] or direct mechanical damage [30][31][32][33][34][35][36][37][38][39] during skiascopy of the heart (during pacemaker implantation) can be a marker of procedure complexity and may positively correlate with troponin levels 31 . Left ventricular failure 40 , right ventricular failure [41][42][43] , or the disparity between physiological degradation of the myocardium and insufficient elimination of its fragments (renal insufficiency) (ref.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Davoodi 34 , troponin T levels were compared between patients undergoing pacemaker versus ICD primo-implantations. The group of patients undergoing ICD implantations had higher levels of troponin T. In this case, the aetiology of this phenomenon is polyfactorial.…”
mentioning
confidence: 99%